Gender-related clinical and management differences in patients with chronic heart failure with reduced ejection fraction - Kocabas, Umut; Kivrak, Tarik; Yilmaz Oztekin, Gulsum Meral; Tanik, Veysel O.; Ozdemir, Ibrahim; Kaya, Ersin; Pehlivanoglu, Seckin (Wiley, 2021)
Aim Gender-related differences have been described in the clinical characteristics and management of patients with chronic heart failure with reduced ejection fraction (HFrEF). However, published data are conflictive in this regard. Methods We investigated differences in clinical and management variables between male and female patients from the ATA study, a prospective, multicentre, observational study that included 1462 outpatients with chronic HFrEF between January and June 2019. Results Study population was predominantly male (70.1%). In comparison to men, women with chronic HFrEF were older (66 +/- 11 years vs 69 +/- 12 years, P < .001), suffered more hospitalisations and presented more frequently with NYHA class III or IV symptoms. Ischaemic heart disease was more frequent in men, whereas anaemia, thyroid disease and depression were more frequent in women. No difference was seen between genders in the use rate of renin-angiotensin system inhibitors, beta-blockers, mineralocorticoid receptor antagonists, or ivabradine, or in the proportion of patients achieving target doses of these drugs. Regarding device therapies, men were more often treated with an implantable cardioverter-defibrillator (ICD) and women received more cardiac resynchronisation therapy. Conclusion In summary, although management seemed to be equivalent between genders, women tended to present with more symptoms, require hospitalisation more frequently and have different comorbidities than men. These results highlight the importance of gender-related differences in HFrEF and call for further research to clarify the causes of these disparities. Gender-specific recommendations should be included in future guidelines in HFrEF.
Keywords: Sex-Differences; Mortality; Guideline; Anemia; Age; Prevalence; Physicians; Prognosis; Survival; Outcomes